From the grounds up : building an export economy in southern Mexico - Lurtz, Casey Marina (Stanford University Press, 2019)
'From the Grounds Up' is a study of how peripheral places grappled with globalization at the end of the nineteenth century. Through extensive use of local archives in the Soconusco district of Chiapas, Mexico, the text redefines the body of actors who integrated Latin America's countryside into international markets for agricultural goods. Alongside plantation owners and foreign investors, a dense but little explored web of indigenous and mestizo villagers, migrant workers, and local politicians quickly adopted and adapted to the production of coffee for export.